Motor unit number index correlates with disability in Charcot-Marie-Tooth disease. Issue 7 (July 2018) - Bas, Joachim; Delmont, Emilien; Fatehi, Farzad; Salort-Campana, Emmanuelle; Verschueren, Annie; Pouget, Jean; Lefebvre, Marie-Noëlle; Grapperon, Aude-Marie; Attarian, Shahram
Highlights: The MUNIX technique estimates axonal loss and the number of remaining functional motor units. The MUNIX sum score correlated with disability in Charcot-Marie-Tooth (CMT) disease as defined by clinical scales. The MUNIX sum score may be proposed as an outcome measure in CMT disease. Abstract: Objective: The aim of this study was to assess the usefulness of motor unit number index (MUNIX) technique in Charcot-Marie-Tooth disease and test the correlation between MUNIX and clinical impairment. Methods: MUNIX technique was performed in the abductor pollicis brevis (APB), the abductor digiti minimi (ADM) and the tibialis anterior (TA) muscles in the nondominant side. A MUNIX sum score was calculated by adding the MUNIX of these 3 muscles. Muscle strength was measured using the MRC (medical research council) scale. Disability was evaluated using several functional scales, including CMT neuropathy score version 2 (CMTNSv2) and overall neuropathy limitation scale (ONLS). Results: A total of 56 CMT patients were enrolled. The MUNIX scores of the ADM, APB and TA muscles correlated with the MRC score of the corresponding muscle (p < 0.01). The MUNIX sum score correlated with the clinical scales CMTNSv2 ( r = −0.65, p < 0.01) and ONLS ( r = −0.57, p < 0.01). Conclusion: MUNIX correlates with muscle strength and clinical measurements of disability in patients with CMT disease. Significance: The MUNIX technique evaluates motor axonal loss and correlates with disability. The MUNIX sum score may be a useful outcome measure of disease progression in CMT.